STEREOTIPE GENDER PADA DONGENG CENDRILLON DALAM KUMPULAN DONGENG LES PLUS BEAUX CONTES KARYA CHARLES PERRAULT - Dian Agustina Pratama (Sekolah Tinggi Bahasa Asing Yapari-ABA, 2021)
The Cendrillon is a fairy tale by Charles Perrault that tells the story of a daughter, her stepmother, and her two sisters. The purpose of this study is to describe the form of stereotypes in the Cendrillon fairy tale. The study used a qualitative descriptive method. The results of gender stereotyping research in the Cendrillon fairy tale show that negative labeling of women arises from social class differences that result in the oppression of bourgeois women in terms of treatment, perspective, and appearance.